Prevalence of Depression Among Nurses of Iran: A Meta-analysis - Parvaneh Isfahani; Rasoul Corani Bahador; Saeid Peirovy; Mahnaz Afshari; Somayeh Samani (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Depression is one of the most common and serious disorders which threatens the mental and physical health of the nurses. This article investigated prevalence of depression among the nurses of Iran using meta-analysis. Methods: This meta-analysis study was done in 2021 using a random-effects model. Data were collected from January 2000 to June 21, 2021, from PubMed, Web of Science, Scopus, Magiran, SID databases and Google Scholar search engine. The data were analyzed using CMA software (Version 2.2.064, the US, Biostate Company). Results: 18 articles were retrieved. The total prevalence rate of depression in Iranian nurses was 12 % [95 % CI= 8.03-17.10]. The highest prevalence rate of depression among nurses was 40.90 % [95 % CI= 32.60-49.70] in Razavi Khorasan, in 2020, and the lowest prevalence rate was 1.70 % [95 % CI= 0.06-4.40] in Lorestan, in 2017. A significant statistical correlation was observed between the prevalence of depression, the sample size, and the work experience (P-value< 0.05). Moreover, we found that the highest rate of depression was based on BDI (Beck's Depression Inventory) questionnaire, and the eastern region of Iran. Conclusion: According to the results, depression has prevailed among one tenth of the Iranian nurses. The finding of this study can help improve the decision- making process for treating depression in Iranian nurses.